2020
DOI: 10.1186/s12870-020-2308-7
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide and indole-3-acetic acid cotreatment regulates the root growth of Brassica napus L. via multiple phytohormone pathways

Abstract: Background: Studies have indicated that graphene oxide (GO) could regulated Brassica napus L. root growth via abscisic acid (ABA) and indole-3-acetic acid (IAA). To study the mechanism and interaction between GO and IAA further, B. napus L (Zhongshuang No. 9) seedlings were treated with GO and IAA accordance with a two factor completely randomized design. Results: GO and IAA cotreatment significantly regulated the root length, number of adventitious roots, and contents of IAA, cytokinin (CTK) and ABA. Treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 59 publications
2
22
0
Order By: Relevance
“…Nguyen et al and Zubo et al [104,105] suggested that the B-ARR gene family members (B-ARR1, B-ARR10, and B-ARR12) play large fundamental roles in the regulation of physiological and transcriptional responses to CK. Eth biosynthesis disruption or signal transduction affects the development of roots, hypocotyls, and seeds [106,107]. The current results revealed the up-regulation of ERS2, EBF1/2, ERF1/2, and MAPK6 in the FO hybrid.…”
Section: Overdominance Of Hormone Signal Transduction Degs Are Involved In the Regulation Of Root Growth Heterosis Of Rapeseedsupporting
confidence: 49%
“…Nguyen et al and Zubo et al [104,105] suggested that the B-ARR gene family members (B-ARR1, B-ARR10, and B-ARR12) play large fundamental roles in the regulation of physiological and transcriptional responses to CK. Eth biosynthesis disruption or signal transduction affects the development of roots, hypocotyls, and seeds [106,107]. The current results revealed the up-regulation of ERS2, EBF1/2, ERF1/2, and MAPK6 in the FO hybrid.…”
Section: Overdominance Of Hormone Signal Transduction Degs Are Involved In the Regulation Of Root Growth Heterosis Of Rapeseedsupporting
confidence: 49%
“…Drought tolerance and improvement of soybean drought tolerance have been promising topics for scientific research. Graphene oxide (GO), a novel nanomaterial as a soil water retention agent, plays a role in the growth and development of plants ( Shen et al, 2018 ; Xie et al, 2020 ). GO not only increased the drought tolerance of in Zea mays L. and Paeonia ostii ( Zhao et al, 2020 ; Lopes et al, 2021 ), but also enhanced the saline-alkali tolerance of Medicago sativa L. ( Chen et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Ratajczak et al revealed that the GO conjugated with a supramolecular including adenosine-5 -triphosphate (ATP), FI-TC (fluorescein isothiocyanate), and survivin molecular beacon (SurMB) can be used as a carrier for gene delivery, and the GO usually interacted with the molecules through the hydrogen bonds' formation and π-π stacking interactions [31,32]. Xie et al, reported the GO-based gene transcript levels of Brassica napus L. (B. napus) [34]. The authors treated the GO with difference concentrations (e.g., 0, 5, 25 mg/L) on B. napus.…”
Section: Direct Influence Of Graphene Oxide On Watermelonmentioning
confidence: 99%